Comparing the Infection Biology of Plasmodiophora brassicae in Clubroot Susceptible and Resistant Hosts and Non-hosts - Liu, Lijiang; Qin, Li; Cheng, Xiaohui; Zhang, Yi; Xu, Li; Liu, Fan; Tong, Chaobo; Huang, Junyan; Liu, Shengyi; Wei, Yangdou (Frontiers in Microbiology, 2020)
The potential infection biology of P. brassicae in resistant hosts and nonhosts is still not completely understood. Clubroot resistance assay on European Clubroot Differentials (ECD) set revealed that ECD10 (Brassica napus) and ECD4 (B. rapa) show a complete resistance to the tested P. brassicae isolate in contrast to highly susceptible hosts Westar (B. napus) and ECD5 (B. rapa). Previously, we used fluorescent probe-based confocal microscopy (FCM) to refine the life cycle P. brassicae and indicate the important time points during its infection in Arabidopsis. Here, we used FCM to systematically investigate the infection of P. brassicae in two resistant host species ECD10 and ECD4 and two nonhost crops wheat and barley at each indicated time points, compared with two susceptible hosts Westar and ECD4. We found that P. brassicae can initiate the primary infection and produce uninucleate primary plasmodia in both resistant hosts and nonhosts just like susceptible hosts at 2 days post inoculation (dpi). Importantly, P. brassicae can develop into zoosporangia and secondary zoospores, and release secondary zoospores from zoosporangia in resistant hosts at 7 dpi, comparable to susceptible hosts. However, during the secondary infection, no secondary plasmodium was detected in the cortical cells of both resistant hosts in contrast to massive secondary plasmodia present in the cortex tissue leading to root swelling in two susceptible hosts at 15 dpi. In both nonhost crops, only uninucleate primary plasmodia were observed throughout roots at 7 and 15 dpi. Quantitative PCR based on DNA revealed that the biomass of P. brassicae has no significant increase from 2 dpi in nonhost plants and from 7 dpi in resistant host plants, compared to the huge biomass increase in susceptible host plants from 2 to 25 dpi. Our study reveals that the primary infection in the root epidermis and the secondary infection in the cortex tissue are respectively blocked in nonhosts and resistant hosts, contributing to understanding of cellular and molecular mechanisms underlying clubroot nonhost and host resistance.